A Review: Natural Resources as Natural Dyes in Pharmaceutical Products - Novelia. D. A, Shintasya; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Several types of natural dyes have been used in pharmaceutical products such as food, beverages, cosmetics and drug additives. Natural dyes are safe and do not cause allergies or irritation to the body. The benefits of natural dyes are as a substitute for synthetic dyes which are safer for the body. The purpose of this article is to discuss natural dyes that are applied or added to pharmaceutical products or the pharmaceutical industry. Data Sources Study Selection: The review method used is by studying the literature relevant to the research. Data sources of this article were selectively taken from Google Schoolar, Pubmed, and Mandeley. Summary of contents of the article: Pharmaceutical products always Use coloring additives for consumer appeal. The addition of dyes to pharmaceutical products such as drugs will make it easier to distinguish between these types of drugs. Dyes that are safe for the body are chosen as a safe alternative in their use. Natural dyes can be derived from plants, minerals, and animals, many plants contain pigments and can be applied to pharmaceutical products such as food, beverages, cosmetics, and medicines. There are many kinds of pigments contained in plants and animals, such as flavonoids, tannins, alkaloids, indigoid, chlorophyll, and carotenoids. Conclusion: The conclusion of this article is that natural dyes cannot only be used as a substitute for dyes that are safe for the body, but natural dyes also have pharmacological properties. The application of natural dyes to food, beverages, cosmetics and medicines does not affect the taste, aroma and texture of the product